2020
DOI: 10.4252/wjsc.v12.i8.857
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell-derived mesenchymal stem cells improved premature ovarian failure

Abstract: BACKGROUND Premature ovarian failure (POF) affects many adult women less than 40 years of age and leads to infertility. According to previous reports, various tissue-specific stem cells can restore ovarian function and folliculogenesis in mice with chemotherapy-induced POF. Human embryonic stem cells (ES) provide an alternative source for mesenchymal stem cells (MSCs) because of their similarities in phenotype and immunomodulatory and anti-inflammatory characteristics. Embryonic stem cell-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 86 publications
(80 reference statements)
1
43
1
Order By: Relevance
“…Our results showed that Prog, Testo, PRL, and E2 were significantly increased after BMMSC treatment, while FSH, LH, and AMH were not significantly different before and after BMMSC treatment. These results are consistent with previous studies reporting the ability of MSCs to restore ovarian structure and sex hormone secretion [ 22 , 27 , 28 ]. Furthermore, previous studies have demonstrated that the number of MSCs in different cell cycle stages can be adjusted by adjusting the concentrations of sex hormones [ 29 , 30 ], suggesting that after BMMSCs restore the secretion of sex hormones, sex hormones may in turn regulate the biological function of MSCs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that Prog, Testo, PRL, and E2 were significantly increased after BMMSC treatment, while FSH, LH, and AMH were not significantly different before and after BMMSC treatment. These results are consistent with previous studies reporting the ability of MSCs to restore ovarian structure and sex hormone secretion [ 22 , 27 , 28 ]. Furthermore, previous studies have demonstrated that the number of MSCs in different cell cycle stages can be adjusted by adjusting the concentrations of sex hormones [ 29 , 30 ], suggesting that after BMMSCs restore the secretion of sex hormones, sex hormones may in turn regulate the biological function of MSCs.…”
Section: Discussionsupporting
confidence: 93%
“…Follicular atresia is related to the apoptosis of granulosa cells, which are large in ovarian follicles; previous studies showed that MSCs improved the apoptosis [ 21 , 22 ]. TUNEL assay was performed to analyse apoptosis, with red staining indicating apoptotic cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…36 In line with this statement, Bahrehbar and colleagues showed that human amniotic fluid MSCs improved ovarian function and folliculogenesis in POF mice. 37 Likewise, in a similar study conducted by Li et al, authors noted that transplantation of human umbilical cord-derived MSCs into the ovaries of menopausal rats improved ovarian reserve, function and resistance to ovarian aging. 38 All of these studies showed an improved ovarian function after the transplantation of different MSC types in the POF models.…”
Section: Discussionmentioning
confidence: 85%
“…POF refers to amenorrhea caused by ovarian follicular degeneration or dysfunction before the age of 40. In most cases, decreased ovarian function and premature ovarian failure are associated with chemotherapy, autoimmune diseases, and operation of the ovary, among other conditions [ 92 ]. Decreased ovarian function not only leads to female infertility, but also affects long-term fertility ability and pregnancy outcomes [ 93 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the transplanted mice generated new offspring. [ 108 ]. This outcome will serve as an important foundation for MSCs in stem cell therapy in infertility cytotherapy.…”
Section: Introductionmentioning
confidence: 99%